Hubungan Durasi dan Posisi Duduk dengan Kejadian Low Back Pain (LBP) pada Mahasiswa Angkatan 2022 - Diah Karlina (Jurnal Praba : Jurnal Rumpun Kesehatan Umum, 2024)
Low back pain (LBP) is pain felt in the lower back due to various reasons. Sitting position is a good position for carrying out activities such as studying, especially when attending lectures. Nursing students are very synonymous with studying in sitting positions for long periods of time. To determine the relationship between sitting position and length of sitting with the incidence of low back pain in Nursing Study Program students at the Columbia Asia College of Health Sciences class of 2022. This research is an observational analytical study with a cross sectional approach using a total sampling method of 34 subjects. There is a relationship between sitting time and position and the incidence of low back pain in Nursing Study Program students at the Columbia Asia College of Health Sciences Class of 2022.